Close Adherence to Mediterranean Diet Reduces Stroke Risk in Women. Issue 2 (11th March 2015) - Kuznar, Wayne
High adherence to a Mediterranean diet pays dividends in preventing stroke, especially ischemic stroke, in women, according to an analysis of the California Teachers Study.